Development Of A Digital Camera-Based Spectrometer For Led Spectrum Analysis - Teo, Choon Kiat (2019)
Charge-Coupled Device (CCD) spectrometer instrument has been widely used in many applications such as photonics research, opto-semiconductor test and measurement, colour imaging science, and many more. The great function of this instrument is the capability of providing essential information about the properties of light which sensed by the instrument CCD sensor.